2007
DOI: 10.1063/1.2721857
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study on secondary electron emission of MgO surface

Abstract: We theoretically investigate secondary-electron-emission properties of MgO when noble gases are incident on the surface. We consider both potential and kinetic emission mechanisms. For the potential emission through Auger neutralization, densities of states and vacuum level are obtained from the first-principles calculations. It is found that secondary-emission coefficients decrease in the following sequence of surface directions; ͑111͒-OHϾ ͑100͒ Ͼ ͑110͒, a tendency that is in agreement with experimental obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 27 publications
3
30
0
Order By: Relevance
“…Details of the calculation can be found in Ref. 25. The computed γ values for the surface with oxygen vacancy are listed in Table II.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of the calculation can be found in Ref. 25. The computed γ values for the surface with oxygen vacancy are listed in Table II.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the peak at 4.2 eV may be owing to the surface F center on the MgO surface. 25 The peak at 6.3 eV is related to the surface inter-band transition. 19 The energy level of the surface F center, F S , is higher than that of the bulk F center, F B .…”
Section: Resultsmentioning
confidence: 99%
“…As an example, attaching hydrogen atoms makes MgO͑111͒ surface insulating. 11 Alternatively, one can control the stoichiometry to neutralize the surface. For instance, the cubic-ZrO 2 ͑100͒ surface becomes insulating if one oxygen atom is removed from the O-terminated surface unit cell.…”
Section: B First-principles Implementationsmentioning
confidence: 99%
“…A higher defect level appears to be advantageous for obtaining a larger SEE yield [10,11]. It was found that occupied defect states such as an oxygen vacancy (Fcenter) lying in the BG of MgO can cause an increase in the SEE yield [12]. The occupied defect state of the C-adsorbed MgO (100) surface could also contribute to an increase in the SEE yield in the case reported herein.…”
Section: Computational Setupmentioning
confidence: 81%